APLIKASI KIDUNG PUJIAN BAHASA DAWAN “SIT KNINO” BERBASIS ANDROID - Tse, Dedi; Naatonis, Remerta Noni; Payong, Yohanes (HOAQ (High Education of Organization Archive Quality) : Jurnal Teknologi Informasi, 2020)
Based on the development of technology years by years, the side of human being’s life cannot separated from the changing of time nowadays, including the development android application form which is studied from book become digital application that can be accessed easily by Smartphone. Android mobile phone is a good medium to develop an application about the content of a book. One of the application worship song “sit knino” is a worship song used by congregations on church or Sunday service and family service. The worship song sit knino has blessed for the growth and matured the faith of congregations who used it. Year by year the quantity of people who used it always raised, so the needed of good quality and quantity also raised, instead of the sit knino worship song used by people right now still on book form and the availability for printed sit knino also limited. Application sit knino worship song on android form is an application which is implemented on android Smartphone that can give easier for Smartphone android user especially for congregations on worship while God’s word service.